PILIHAN STRATEGI PENGEMBANGAN WISATA GILI LABAK KECAMATAN TALANGO KABUPATEN SUMENEP - Dedy Arfiyanto; Isnani Yuli Andini (Fakultas Ekonomi dan Bisnis, 2017)
The presence of the Suramadu bridge has a direct impact on the economic side, this can be demonstrated by the increase in gross domestic income which increases from year to year. Efforts to maximize the potential of the region other than agriculture, plantation, and mining and marine industries, Pertingnya is to maximize the potential of the beauty of the natural panorama, the condition of the panorama of nature is quite a lot of scattered in various regions both inland and in the archipelago so far, still constrained by the existing infrastructure, the infrastructure is the lack of proper transport and safe to connect between the island, , Island water supply and other supporting facilities. The limited infarasturcure problem led to the development of island tourism only a planning document without realization.Data collected in this study include primary data and secondary data. The results of the study indicate a strategy is needed to increase the growth rate of tourist visits with faster time (second year is greater than the first year and beyond), quality improvement becomes the strength factor to maximize the utilization of all opportunities. Keywords : Strategy, Tourism Development